(untitled) (Environment & Health, 2018)
Objective: We performed a hygienic assessment of the air pollution level with dust particulate matters (PM10 and PM2.5) in Kyiv. Materials and methods: Instrumental measurements of PM10 and PM2.5 concentrations in the atmospheric air were carried out from January to September 2018. The stationary monitoring station for suspended particles is located at the address: 50 Popudrenko str., Kyiv and equipped with APDA-371 (HORIBA) analyzers which provide automatic continuous measurement of concentrations with hourly averaging of data. The obtained findings were processed with the help of the software package Statistica, the results were compared with the maximum values recommended by WHO and Directive 2008/50/EC. Results and conclusions: Analysis of data, obtained in 2018 (January - September), allowed to draw a conclusion that the levels of air pollution with PM10 and PM2.5 in Kyiv exceeded the maximum ones, recommended by WHO or Directive 2008/50 / EC. Average concentrations of PM10 were at the level of 36 ± 0.4 mg / m3, PM2.5 - 21 ± 0.2 mg / m3; the number of days with an excess of the average daily concentration for PM10 was 43 days (19%), for PM2.5 - 61 days (25%); maximum monthly concentrations of PM2.5 were observed during the heating season - from January to March and were at the level of 26-27 mg / m3. According to the results of the correlation analysis, a significant correlation was found between the concentrations of PM2.5 and PM10 (r = 0.79, p < 0.005); PM2.5 = 0.66 * PM10. The obtained results indicate the need to establish standards for PM10 and PM2.5 in Ukraine and to include the dust particulate matters into the mandatory monitoring program of atmospheric air quality.